The Küng is dead, long live the Küng: The value of Hans Küng"s theology - Macallan, Brian C. (HTS teologiese studies, 2022)
Hans Küng’s influence on the church and its theology in the 20th-century theology has been immense. It has also not been without controversy, from his role at Vatican II to the loss of his teaching licence and his often-combative relationship with Benedict XVI. In 2021 Hans Küng died at the age of 93. This article offers an autoethnographic response to his work experienced over roughly two decades, from my early days as a theology student, struggles with Church authority, to personal illness. Küng’s work provided a reference point for many of the challenges faced in ‘being a Christian’. The first part of the article establishes an autoethnographic methodological approach, leading to the exploration of four key texts from Küng, highlighting their general value while also noting their connection to my own theological journey. By examining Küng’s work in connection with my own life, I hope to make an argument for the continued relevance of his core ideas, while also introducing his life and work more broadly to those unfamiliar with Küng and his contribution.Contribution: This article offers key insights into the theology and relevance of Hans Küng’s work from an autoethnographic perspective. It engages with some of the key texts in Küng’s oeuvre, with the goal of personal and societal changes in mind. It has been written in light of Küng’s recent death in 2021.